Genetically determined diseases associated with an increased risk of sudden cardiac death: etiology, diagnosis and treatment - S. P. Leshchinsky (Сеченовский вестник)
At the moment the problem of cardiovascular disease received much attention worldwide. Among other diseases of the cardiovascular system these occupy a special place, associated with a high risk of sudden cardiac death. This group of diseases (according to the statistics) occupies one of the top lines in leading causes of death in developed countries. This review displayes moments of etiology, diagnosis and treatment of certain diseases that can lead to sudden death in patients.